ANALYSIS OF THE COMPANY’ POTENTIAL FINANCIAL LOSS IMPACT OF TRADE RECEIVABLES - Biantara, Dheny; Lesmana, Iwan; Handayani, Sri; Setiono, Bambang (Indonesian Journal of Accounting and Governance, 2023)
The problems with receivables faced by the company experienced many obstacles so thatinaccurate recording and technology systems that had not been integrated between units became one ofthe obstacles they faced. This study aims to determine the accounting information system on accountsreceivable which is related to its role in the process of sustainable development of a company. Themethod used in this study is a qualitative - descriptive method. Data collection was carried out byinterview, observation and documentation techniques. Data analysis was carried out by means of datareduction, data representation, and drawing conclusions. The results showed that the accountsreceivable accounting information system procedures at several companies had different characteristicsbut remained the same in terms of the problems faced, especially during the past Covid-19 outbreakwhere many companies, both self-served and government-owned, experienced serious problems in theprocess of collecting their accounts receivable. .Standard operating procedures for accounts receivablethat are clear and separated from existing functions and have a very complete job desk for their parts aswell as well-documented records can expedite the process of information on the condition ofreceivables so that strategic steps can be taken to generate cash inflows for company which willultimately improve the condition of the company's financial performance to be able to continue todevelop sustainably.